Formulation And Evaluation Of Emulgel Of An Antifungal Drug For Topical Drug Delivery (Journal of Pharmaceutical Negative Results, 2023)
Topical drug delivery system improved bioavailability, reduced side effects, more uniform plasma levels, longer duration of action, resulting in a reduction in dosing frequency and improve therapy due to plasma levels up to the end of the dosing interval compared to a decline in plasma levels with conventional oral dosage form. Emulgel are generally used where the other systems of drug administration fails to directly treat cutaneous disorders such as fungal infections, acne, psoriasis etc.Materials and methods: Fluconazole emulgel was optimized based on Design-Expert® software using central composite design (CCD) making Fourteen formulations using jojoba oil and liquid paraffin, Methylparaben, Propylparaben and Triethanolamine.Results and Discussions: - The spreadability test range find from 8.9 g.cm/min to 14.87 g.cm/min for the formulations F1 and F14, respectively. Formulations having low amount of jojoba oil and liquid paraffin had the high spreadability index. As the viscosity of the gel increased, the release of the drug was expected to be slower. Complete drug release (100%) was achieved at the 3rd hr for the formulations F1, F8, F7 and F14 released more than 80 % of the drug and in vitro results showed that an emulgel formulation can be a potential candidate for the delivery of fluconazole for the skin disease, with better in vitro physical, using jojoba oil and liquid paraffin as drug carriers. SEM analysis of emulgel shows the uniform structure of emulgel formulation.